MAO-free and extremely active catalytic system for ethylene tetramerization - Kim, Tae Hee; Lee, Hyun Mo; Park, Hee Soo; Kim, Sung Dong; Kwon, Su Jin; Tahara, Atsushi; Nagashima, Hideo; Lee, Bun Yeoul (Applied Organometallic Chemistry, 2019)
The original Sasol catalytic system for ethylene tetramerization is composed of a Cr source, a PNP ligand, and MAO (methylaluminoxane). The use of expensive MAO in excess has been a critical concern in commercial operation. Many efforts have been made to replace MAO with non-coordinating anions (e.g., [B(C 6 F 5 ) 4 ] − ); however, most of such attempts were unsuccessful. Herein, an extremely active catalytic system that avoids the use of MAO is presented. The successive addition of two equivalent [H(OEt 2 ) 2 ] + [B(C 6 F 5 ) 4 ] − and one equivalent CrCl 3 (THF) 3 to (acac)AlEt 2 and subsequent treatment with a PNP ligand [CH 3 (CH 2 ) 16 ] 2 C(H)N(PPh 2 ) 2 (1) yielded a complex presumably formulated as [1-CrAl (acac)Cl 3 (THF)] 2+ [B(C 6 F 5 ) 4 ] − 2 , which exhibited high activity when combined with iBu 3 Al (1120 kg/g-Cr/h; ~4 times that of the original Sasol system composed of Cr (acac) 3 , iPrN(PPh 2 ) 2 , and MAO). Via the introduction of bulky trialkylsilyl substituents such as –SiMe 3 , –Si(nBu) 3 , or –SiMe 2 (CH 2 ) 7 CH 3 at the para-position of phenyl groups in 1 (i.e., by using [CH 3 (CH 2 ) 16 ] 2 C(H)N[P(C 6 H 4 -p-SiR 3 ) 2 ] 2 instead of 1), the activities were dramatically improved, i.e., tripled (2960–3340 kg/g-Cr/h; more than 10 times that of the original Sasol system). The generation of significantly less PE (<0.2 wt%) even at a high temperature is another advantage achieved by the introduction of bulky trialkylsilyl substituents. NMR studies and DFT calculations suggest that increase of the steric bulkiness on the alkyl-N and P-aryl moieties restrict the free rotation around (alkyl)N–P (aryl) bonds, which may cause the generation of more robust active species in higher proportion, leading to extremely high activity along with the generation of a smaller amount of PE.
Keywords: 1-octene; Catalytic system; Chromium catalysts; Commercial operation; Coordinating anions; High temperature; Methylaluminoxane; Tetramerization; 1-octene production; chromium catalyst; ethylene tetramerization; PNP ligand derivative